Hydrazone and Hydrazide Chelates of Ni(II) and Cu(II) - Kant Jha, Bijay; Jha, S.; Kant Jha, Amar (Asian Journal of Chemistry, 2010)
Co-ordination compounds of general formulae ML2 and ML2B2 [whereM = Ni(II) or Cu(II), L = mono deprotonated o-vaniline hydrazone(OVHyH), o-vaniline phenyl hydrazone (OVPhHyH) salicylidinehydrazide (SAHyH2) and salicylidine phenyl hydrazide (SAPhHyH2),B =α, β or γ -picoline] have been synthesised and characterised based onthe elemental analysis, conductance, magnetic and spectral data.